Unravelling the role of the combined effect of metallic charge transfer channel and SiOx overlayer in the Zr/Si-Fe2O3:Au:SiOx nanorod arrays to boost photoelectrochemical water splitting - Koh, Tae Sik; Anushkkaran, Periyasamy; Dhandole, Love Kumar; Mahadik, Mahadeo A.; Chae, Weon-Sik; Lee, Hyun Hwi; Choi, Sun Hee; Jang, Jum Suk (Elsevier BV, 2024)
Hematite (a-Fe2O3) based photoanodes have been extensively studied due to various intriguing features that make them viable candidates for a photoelectrochemical (PEC) water splitting photoanode. Herein, we propose a Zr-doped Fe2O3 photoanode decorated with facilely spin-coated Au nanoparticles (NPs) and microwave-assisted attached Si co-doping in conjunction with a SiOx overlayer that displayed a remark-able photocurrent density of 2.01 mA/cm2 at 1.23 V vs. RHE. The kinetic dynamics at the photoelectrode/-electrolyte interface was examined by employing systematic electrochemical investigations. The Au NPs played a dual role in increasing PEC water splitting. First, the Schottky interface that was formed between Au NPs and Zr-Fe2O3 electrode ensured the prevention of electron flow from the photoanode to the metal, increasing the number of available charges as well as suppressing surface charge recombination. Second, Au extracted photoholes from the bulk of the Zr-Fe2O3 and transported them to the outer SiOx overlayer, while the SiOx overlayer efficiently collected the photoholes and promoted the hole injection into the electrolyte. Further, Si co-doping enhanced bulk conductivity by reducing bulk charge transfer resistance and improving charge carrier density. This study outlines a technique to design a metallic charge transfer path with an overlayer for solar energy conversion.(c) 2023 Science Press and Dalian Institute of Chemical Physics, Chinese Academy of Sciences. Published by ELSEVIER B.V. and Science Press. All rights reserved.